Carbon stored by furnishing wood-based products: An Italian case study - Negro, Francesco; Bergman, Richard (Maderas. Ciencia y Tecnología, 2019)
The concentration of atmospheric carbon dioxide is constantly rising, with severe effects on global climate change. To mitigate impacts of climate change, the role of forest in terms of carbon sequestration are well-known as trees naturally pull CO2 from the atmosphere as they grow. Contrarily, only recently the carbon mitigation value of wood-based products in buildings has been recognized. Buildings are a fundamental sector for wood-based products, both in terms of volume and service life length. In particular, furnishings in housing include high quantities of wood-based products; they are usually made, partly or entirely, by solid wood or by wood-based panels such as plywood, particleboard and medium density fiberboard. These wood furnishings store biogenic carbon during their service life. In this context, the present study investigated the amount of carbon stored by furnishing wood-based products for an apartment in Torino, Italy. The overall amount, determined according to European Standard, resulted in 3531 kg of CO2-equivalents stored. This corresponds to 45,8 kg/m2 of indoor walkable area; simulating lower and higher intensity usages of wood-based products provided carbon storage values of 35,1 and 55,3 kg/m2, respectively. On the whole, the present study gave an order of magnitude of the role played in carbon storage by furnishing wood-based products in building and illustrates their relevance in mitigating climate change.